Quasi‐Solid Electrolyte Design and In Situ Construction of Dual Electrolyte/Electrode Interphases for High‐Stability Zinc Metal Battery. Issue 25 (10th May 2022) - Guo, Shan; Qin, Liping; Hu, Chao; Li, Lanyan; Luo, Zhigao; Fang, Guozhao; Liang, Shuquan
Abstract: Interfacial stability and compatibility in rechargeable metal batteries (RMBs) is still made difficult by deterioration under electrochemical dynamic operation due to the activeness of the metallic anodes and their spontaneous reaction with the liquid electrolyte. Herein, robust quasi‐solid zinc metal batteries enabled by in situ formation of stable dual electrolyte/electrode interphases with an electrochemical stability during cycling are reported. The quasi‐solid electrolyte sufficiently transfers the zinc ions due to the construction of the unobstructed ions transportation network composed of intergranular liquid phase migration and interlayer diffusion. The distinctive in situ formation of dual interphases, specially with heterojunction charge aggregation, cleverly settles the issues of interfacial compatibility, which achieves a stable Zn 2+ plating/stripping of more than 3000 h and far exceeding the transient 250 h of its liquid counterpart. This design strategy for quasi‐solid electrolytes is expected to advance the development of the quasi‐solid battery field. Abstract : A robust quasi‐solid zinc metal battery enabled by in situ formation of dual electrolyte/electrode interphases is reported. The distinctive in situ formation of dual interphases can cleverly settle the issues of interfacial compatibility.